Mortality prediction using CHADS2/CHA2DS2-VASc/R2CHADS2 scores in systolic heart failure patients with or without atrial fibrillation. Issue 43 (October 2017) - Chen, Yung-Lung; Cheng, Ching-Lan; Huang, Jin-Long; Yang, Ning-I; Chang, Heng-Chia; Chang, Kuan-Cheng; Sung, Shih-Hsien; Shyu, Kou-Gi; Wang, Chun-Chieh; Yin, Wei-Hsian; Lin, Jiunn-Lee; Chen, Shyh-Ming
Abstract : Abstract: The CHADS2, CHA2 DS2 -VASc, and R2 CHADS2 scores are well-known predictors of stroke caused by atrial fibrillation (AF), but no studies have evaluated their use for stratifying all-cause mortality risk in patients discharged for systolic heart failure (SHF) with or without AF. This study analyzed data in the Taiwan Society of Cardiology—heart failure with reduced ejection fraction (TSOC-HFrEF) registry. These data were obtained by a prospective, multicenter, observational survey of patients treated at 21 medical centers in Taiwan after hospitalization for acute, pre-existing or new onset SHF from May, 2013 to October, 2014. During 1 year follow-up, 198 patients were lost follow-up, and final 1311 (86.8%) patients were included for further analysis. During the follow-up period, 250 (19%) patients died. Multivariate analysis revealed that body mass index, thyroid disorder, valvular surgery history, chronic kidney disease (CKD), and scores for CHADS2, CHA2 DS2- VASc, and R2 CHADS2 were significant independent predictors of mortality in the overall population of SHF patients (all P < .05) The c-indexes showed that CHADS2, CHA2 DS2 -VASc, and R2 CHADS2 scores were significantly associated with mortality in SHF patients with or without AF (all P < 005). However, R2 CHADS2 had significantly higher accuracy in predicting mortality in all SHF patients compared with CHADS2 and CHA2 DS2 -VASc (DeLong test, P < .0001), especially in SHF without AF (DeLong test, P = .0003). Scores for CHADS2, CHA2 DS2 -VASc, and R2 CHADS2 can be used to predict 1-year all-cause mortality in SHF patients with or without AF. For predicting all-cause mortality in SHF patients, R2 CHADS2 is more accurate than CHADS2 and CHA2 DS2 -VASc. Abstract : Supplemental Digital Content is available in the text